Eksplorasi Model Project-Based Learning Berbasis Media Sosial dalam Pembelajaran Keterampilan Argumentatif Bahasa - Rizqien, Nadhifatur; Mujianto, Gigit (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
The main objective of this study is to describe the exploration of the social media-based project-based learning (PjBL) model that can support the development of students' argumentative skills in learning Indonesian. The qualitative approach method with descriptive analysis methods with research respondents being class VIII.3 students at SMPN 1 Larangan. There is 1 model teacher with a population of 30 students. This focuses on the learning patterns used with a digital basis, but also to understand the effectiveness of implementing innovative learning models. The results show that the exploration of the social media-based Project-Based Learning (PjBL) model can improve argumentative skills and increase student activeness in learning including digital literacy, especially to hone argumentative skills. Exploration of the social media-based PjBL model provides an innovative alternative in learning Indonesian, especially to hone argumentative skills. With the right guidance, students are not only skilled at arguing, but also have the ability to use social media positively as a learning tool.